The Effect of Using Google Sites Media on Understanding and Problem-Solving Ability in Basic Programming Learning - Firman Wahyudi Ahmad, Muhajir, Edy Widayat (Lembaga Bale Literasi, 2025)
Conventional teaching approaches contribute to students' poor conceptual comprehension and problem-solving abilities, which is one of the ongoing issues in basic programming education. The purpose of this research is to determine if and how students' comprehension and ability to solve problems in introductory computer science courses are affected by the usage of Google Sites as a learning platform. Participants were pupils from Proppo 1 Public High School, and the study's methodology was a quasi-experimental one employing a nonequivalent control group design. Instruments such as assessments of concept understanding and problem-solving skills were used to gather data, which was then statistically analyzed using IBM SPSS software. The results show that students' ability to understand concepts (sig. 0.045) and solve problems (sig. 0.014) is much enhanced when Google Sites is used in the classroom. In order to fulfil the needs of the 21st century, particularly in terms of digital literacy and higher-order thinking abilities, these results demonstrate that web-based technology, and Google Sites in particular, may be a relevant and successful learning option. To sum up, Google Sites promotes critical thinking, self-directed learning, and enhanced comprehension and problem-solving abilities among pupils. The findings should not be applied to other schools or subjects without further investigation. Consequently, it is advised to do more study on various topics, levels, and learning methods.